Clinical and Fundamental Research Progressions on Tumor-Infiltrating Lymphocytes Therapy in Cancer - Jiandong Hu; Mengli Jin; Weihong Feng; Barbara Nassif-Rausseo; Alexandre Reuben; Chunhua Ma; Gregory Lizee; Fenge Li (Vaccines)
Malignant tumors represent a significant threat to human health. Among the various therapeutic strategies available, cancer immunotherapy—encompassing adoptive cell transfer (ACT) and immune checkpoint blockade therapy—has emerged as a particularly promising approach following surgical resection, radiotherapy, chemotherapy, and molecular targeted therapies. This form of treatment elicits substantial antigen-specific immune responses, enhances or restores anti-tumor immunity, thereby facilitating the control and destruction of tumor cells, and yielding durable responses across a range of cancers, which can lead to the eradication of tumor lesions and the prevention of recurrence. Tumor-infiltrating lymphocytes (TILs), a subset of ACT, are characterized by their heterogeneity and are found within tumor tissues, where they play a crucial role in mediating host antigen-specific immune responses against tumors. This review aims to explore recent advancements in the understanding of TILs biology, their prognostic implications, and their predictive value in therapeutic contexts.